(untitled) (International Journal of Engineering and Computer Science, 2015)
In the recent era of the world of computing, cloud has become a trend-setter by providing the ease of storing and sharing the data in enormous volumes. Cloud computing has evolved as a boon to its users by not only relieving them from the burden of storing and maintaining huge data but also give them the feel that their data is straightforwardly accessible from anywhere across the globe. The users will no more have the physical possession of their data, which will mount the security concerns of storing the data in cloud, which is a third party server whose location is not known to the user. Therefore verification of data to ensure the storage correctness becomes a significant task in cloud. As the users of cloud are free from the burden of storing and maintaining their data, they must also be free to use their data without worrying about the need for any integrity checking. So cloud uses a Third Party Auditor (TPA) who has the capability for verifying the data for its consistency. In this paper we will discuss about the various techniques that can be adopted by the TPA in ensuring the storage correctness of dynamic data in cloud.